2006
DOI: 10.1038/sj.ebd.6400446
|View full text |Cite
|
Sign up to set email alerts
|

Implant retained or conventional dentures, which give more patients satisfaction?

Abstract: Design This was a randomised controlled trial (RCT) set in a dental hospital. Intervention The implant group (IG) had two implants placed in the interforaminal region of the lower jaw followed (after healing) by a denture fixed to the implants by a ball attachment mechanism. In the conventional dentures group (CG), dentures were constructed using conventional replacement denture techniques. Patients in the IG had conventional upper dentures made in the same fashion. Outcome measure The performance of the dentu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 8 publications
(8 reference statements)
2
7
0
Order By: Relevance
“…The present work also showed a significant improvement of OHRQoL in retained or fixed complete denture wearers, as previously reported in another study, which used the OHIP and OIDP as evaluation tools [31]. In addition, two studies using the OHIP did not demonstrate any difference in OHRQoL between conventional and implant-retained complete denture wearers [35,36]. On the other hand, before treatment, participants that accepted implant treatment presented an initially poorer OHRQoL than that of conventional full removable denture wearers.…”
Section: Discussionsupporting
confidence: 90%
“…The present work also showed a significant improvement of OHRQoL in retained or fixed complete denture wearers, as previously reported in another study, which used the OHIP and OIDP as evaluation tools [31]. In addition, two studies using the OHIP did not demonstrate any difference in OHRQoL between conventional and implant-retained complete denture wearers [35,36]. On the other hand, before treatment, participants that accepted implant treatment presented an initially poorer OHRQoL than that of conventional full removable denture wearers.…”
Section: Discussionsupporting
confidence: 90%
“…1). Hence, it can be concluded that placement of a provisional implant‐supported crown improves “OHRQoL.” This is in agreement with Berretin‐Felix et al (2008) and Jokstad (2006). Whether this is affected by the immediate restoration with a provisional crown, or due to the implant placement alone, cannot be specified because a non‐restored control group was missing.…”
Section: Discussionsupporting
confidence: 69%
“…29 With a significant increase in all seven domains at 1 year follow-up an overall improvement was clearly demonstrated in this study. 74 An important limitation of the current study is that our results may not fully reflect current practice because no biomaterials were used in conjunction to immediate implant placement. 74 An important limitation of the current study is that our results may not fully reflect current practice because no biomaterials were used in conjunction to immediate implant placement.…”
Section: Discussionmentioning
confidence: 89%